Hierarchical Phosphorylation of δ-Opioid Receptor Regulates Agonist-induced Receptor Desensitization and Internalization - Maestri-El Kouhen, Odile (2000)
Treatment of HEK293 cells expressing the δ-opioid receptor with agonist [d-Pen(2,5)]enkephalin (DPDPE) resulted in the rapid phosphorylation of the receptor. We constructed several mutants of the potential phosphorylation sites (Ser/Thr) at the carboxyl tail of the receptor in order to delineate the receptor phosphorylation sites and the agonist-induced desensitization and internalization. The Ser and Thr were substituted to alanine, and the corresponding mutants were transiently and stably expressed in HEK293 cells. We found that only two residues, i.e. Thr(358) and Ser(363), were phosphorylated, with Ser(363) being critical for the DPDPE-induced phosphorylation of the receptor. Furthermore, using alanine and aspartic acid substitutions, we found that the phosphorylation of the receptor is hierarchical, with Ser(363) as the primary phosphorylation site. Here, we demonstrated that DPDPE-induced rapid receptor desensitization, as measured by adenylyl cyclase activity, and receptor internalization are intimately related to phosphorylation of Thr(358) and Ser(363), with Thr(358) being involved in the receptor internalization.